Многомерная задача линейного программирования - Cirba, S. (Mathematical Modelling and Analysis, 1996)
“Многомерная задача линейного программирования”Mathematical Modelling Analysis, 1(1), p. 65-66.Article in Russian.First Published Online: 14 Oct 2010